2001
DOI: 10.1021/jf000725m
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Test for the Effectiveness of Antioxidants as Inhibitors of Thiyl Radical-Induced Reactions with Unsaturated Fatty Acids

Abstract: Attacks of thiyl radicals on the double bonds of unsaturated fatty acids lead to stereomutation (cis-, trans-isomerization without double-bond migration) and addition reactions (thioether formation). On the basis of these findings, an in vitro test system has been developed which allows the study of the effectiveness of specific antioxidants in preventing thiyl radical-induced attacks on unsaturated fatty acids. The test involves thermal treatment of a mixture of oleic (cis-9-octadecenoic) acid and 1-tetradeca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 13 publications
0
24
0
1
Order By: Relevance
“…various natural products, and exhibits a wide variety of biological effects, including antibacterial, 11 antioxidant, 12,13 antifungal and antimalarial, 14 and antiherpetic action. 15 In addition, the antiviral capacity of GA is related to its antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…various natural products, and exhibits a wide variety of biological effects, including antibacterial, 11 antioxidant, 12,13 antifungal and antimalarial, 14 and antiherpetic action. 15 In addition, the antiviral capacity of GA is related to its antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…21 Herein, the cis-trans isomerization of fatty acid residues in LUVs by thiyl radicals in the absence and presence of various antioxidants has been extensively studied and the data have been rationalized based on kinetic data available in the literature from pulse radiolysis. [20][21][22] Using the methanolic injection method, it is possible to affect the liposome size 31 and in our experiments the preparation of vesicles was performed to reproduce the same size of vesicles obtained by the extrusion technique, ascertained by Dynamic Light Scattering (DLS) measurements. 32 It was gratifying to find that similar dose profiles of the cis-trans isomerization by HOCH 2 CH 2 S• radicals (MS•) were observed for extruded DOPC vesicle suspensions added with 1.2 M MeOH and vesicle suspensions obtained by an appropriate methanolic DOPC injection in water (dashed line in Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…We observed that the ability to scavenge thiyl radicals generated by Îł-radiolysis in aqueous vesicle suspensions increases along the series ArOH < retinol < UH 3 < AH 2 , a different order to that observed in organic solutions or using multilamellar vesicles (MLVs) described in previous studies. [20][21][22] The proposed anti-isomerizing activity is based not only on the relative chemical reactivity of the antioxidants, but also on their partition coefficient, i.e., the localization of the free radical scavengers in the aqueous or lipid compartment. …”
Section: Introductionmentioning
confidence: 99%
“…Gallic acid (3,4,5-trihydroxybenzoic acid, GA), an intermediate component of plant metabolism from the hydrolysis of tannins (5), has been associated with a wide variety of biological actions including antioxidant (6), antibacterial (7), antifungal and antimalarial (8), and antiherpetic action (5). The main interest in GA is related to its antitumoral activity.…”
Section: Introductionmentioning
confidence: 99%